2021
DOI: 10.1111/jfpp.15851
|View full text |Cite
|
Sign up to set email alerts
|

Textural and sensory properties of wheat bread fortified with nettle ( Urtica dioica L.) produced by the scalded flour method

Abstract: The main aim of the study was to investigate the texture and sensory properties of wheat bread with nettle infusion, which was incorporated into the dough recipe in the process of wheat flour scalding. The addition of nettle, at the following concentration: 10, 20, 30, and 40 mg/ml, was introduced into the dough as an infusion in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…A significantly smaller loaf volume compared to the control sample was noted for bread with 3% and higher TO share, and a significantly higher crumb specific mass, for bread with a 5% and 6% TO share. A similar trend was observed after the addition to the recipe of wheat bread of dried crushed leaves of the Moldavian dragonhead (Dracocephalum moldavica) [34], leaves of rockrose (Cistus incanus) [35], leaves of nettle (Urtica dioica) [40], dried ground berries of sumac (Rhus co-riaria) [31], powdered onion waste [33], turmeric (Curcuma longa) [41], and chia seeds (Salvia hispanica) [38]. Czaja et al [39] and Pasrija et al [42] found no significant effect of the addition of microencapsulated onion peel extracts and green tea leaf extracts on bread yield, but this could be due to the relatively low proportion of these additives in the bread recipe.…”
Section: Yield Volume and Density Of Bread Crumb Enriched With Taraxacum Officinalesupporting
confidence: 70%
See 4 more Smart Citations
“…A significantly smaller loaf volume compared to the control sample was noted for bread with 3% and higher TO share, and a significantly higher crumb specific mass, for bread with a 5% and 6% TO share. A similar trend was observed after the addition to the recipe of wheat bread of dried crushed leaves of the Moldavian dragonhead (Dracocephalum moldavica) [34], leaves of rockrose (Cistus incanus) [35], leaves of nettle (Urtica dioica) [40], dried ground berries of sumac (Rhus co-riaria) [31], powdered onion waste [33], turmeric (Curcuma longa) [41], and chia seeds (Salvia hispanica) [38]. Czaja et al [39] and Pasrija et al [42] found no significant effect of the addition of microencapsulated onion peel extracts and green tea leaf extracts on bread yield, but this could be due to the relatively low proportion of these additives in the bread recipe.…”
Section: Yield Volume and Density Of Bread Crumb Enriched With Taraxacum Officinalesupporting
confidence: 70%
“…The exception was crumb hardness, which increased linearly from 7.1 (control sample) to 12.1 N (sample with 6% TO). The increase in the crumb hardness of wheat bread was also caused by the addition to its recipe of leaves of dried rockrose (Cistus incanus) [35], dried leaves of Moldavian dragonhead (Dracocephalum moldavica) [34], berries of sumac (Rhus coraria) [31], dried leaves of nettle (Urlica dioica) [40], turmeric (Curcuma longa) [41], micronized extracts of green tea leaves [42], and artichoke (Cynara scolymus) [43]. The demonstrated increase in the crumb hardness of wheat bread enriched with plant raw materials may be explained by the presence of fiber and polyphenols.…”
Section: Textural Characteristics Of Bread Enriched With Taraxacum Officinalementioning
confidence: 99%
See 3 more Smart Citations